Differentiating the cognitive development of early-term births in infants and toddlers: a cross-sectional study in China - Jing Hua; Jie Sun; Zhijuan Cao; Xiaotian Dai; Senran Lin; Jialin Guo; Guixiong Gu; Wenchong Du (BMJ Open)
Objectives This study aimed to explore the cognitive development of low-risk children during early childhood for early-term births at 37 and 38 weeks of gestation compared with full term births at 39–41 weeks of gestation.Setting and participants We conducted a cross-sectional study in Shanghai, one of the largest cities in China. A total of 1444 children from singleton pregnancies born at term gestation were included in the study.Measures The cognitive outcomes of the subjects were measured using the cognitive subtest of Bayley Scales of Infant and Toddler Development, Third Edition (BSID-III) across three cities in China. We analysed the association between gestational age and cognitive development during infancy and toddler stages using multivariate linear modelling.Results The cognitive development scores for infants born at 37 gestational weeks were significantly lower than those born at 39–41 gestational weeks (β=−2.257, 95% CI −4.280 to −0.235; p<0.05) after adjusting for children’s and maternal characteristics, as well as socio-economic factors. However, there were no significant differences in cognitive ability between infants born at 38 gestational weeks compared with their full-term counterparts (p>0.05). Moreover, these effects were not found in toddlers (between 17 and 48 months of age) after adjusting for the possible confounders (p>0.05).Conclusions Infants born at 37 weeks of gestation exhibited weaker cognitive ability compared with those born at 39–41 weeks of gestation. Our findings provide evidences for the close monitoring of potential developmental problems in early-term children, especially those born at 37 gestational weeks.